SecureClean Pro: A Vehicle Detailing Service Booking System Using Enhanced One-Time Password (OTP-X) for Azim AIC Sdn. Bhd. - THIRU KUMAR, SATHIASEELAN; DR. NUR ZIADAH BINTI HARUN, (Applied Information Technology And Computer Science, 2024)
SecureClean Pro is a system that encompasses AZIM AIC SDN BHD’s vehicle detailing services booking process management integrated with multifactor authentication. Drawbacks in the existing booking system of the company such as task assignment delays, miscommunications, and inadequate security measures, risking client data confidentiality, integrity and weak authentication. To resolve the deficiencies, the system incorporates Optical Character Recognition (OCR) to ease customer data inputting and verification method, enhanced One-Time Password (OTP-X), and authentication approval link to implement robust multifactor authentication as an extra layer of authentication. Adopting Agile methodology as development methodology and using Laravel framework, this web-based system caters the role of administrator, staff, and customers respectively for managing, get assigned and making the booking. Thus, SecureClean Pro can perform robust user authentication, and improving daily booking operations for the company, making it an essential solution for the underlined problems and business growth.